Crystallinity, thermal and pasting properties of starches from different potato cultivars grown in Brazil - dos Santos, Thais Paes R. [UNESP] (2016)
Starches from different potato cultivars were characterized as amylose and phosphorus content, crystallinity, thermal and paste properties. Statistical analysis of amylose content showed difference between starches samples and the cultivars Asterix and BRS Clara showed higher contents than others. Phosphorus content ranged from 633 to 966.7 mg kg-1. The X-ray diffraction analysis showed that the crystallization of potato starches can be classified as B-type X-ray pattern, presenting crystallinity index ranging from 20.02% to 21.59%. Regarding thermal properties, the onset temperature did not show statistical difference between starch samples, in gelatinization and retrogradation analysis. As expected there was a significant decrease in peak temperature and enthalpy after the retrogradation of starches. For the pasting properties results showed significant difference in all cultivars. Pearson correlation coefficients showed that amylose content was negatively correlated to the onset, peak and final temperature of gelatinization, final temperature of retrogradation and pasting temperature. Phosphorus content was positively correlated to crystallinity index, peak viscosity and breakdown. Starches extracted from potato varieties showed different characteristics which can be useful to food and related industries that make use of potato starch, allowing wide options of use in various sectors of industrial application in Brazil.